Deposition and Characterization of CVD-Grown Ge-Sb Thin Film Device for Phase-Change Memory Application. (23rd April 2012) - Huang, C. C.; Gholipour, B.; Knight, K.; Ou, J. Y.; Hewak, D. W.
Abstract : Germanium antimony (Ge-Sb) thin films with tuneable compositions have been fabricated on SiO2 /Si, borosilicate glass, and quartz glass substrates by chemical vapour deposition (CVD). Deposition takes place at atmospheric pressure using metal chloride precursors at reaction temperatures between 750 and 875°C. The compositions and structures of these thin films have been characterized by micro-Raman, scanning electron microscope (SEM) with energy dispersive X-ray analysis (EDX) and X-ray diffraction (XRD) techniques. A prototype Ge-Sb thin film phase-change memory device has been fabricated and reversible threshold and phase-change switching demonstrated electrically, with a threshold voltage of 2.2–2.5 V. These CVD-grown Ge-Sb films show promise for applications such as phase-change memory and optical, electronic, and plasmonic switching.